Tandem workshop on the Nagoya Protocol on access and benefit-sharing & the multi-lateral system of access and benefit-sharing under the International Treaty on Plant Genetic Resources for Food & Agriculture (ITPGRFA), 29th September 2017, Paro, Bhutan. - Dorji, C.; Nirola, M.P.; Vernooy, Ronnie (National Biodiversity Centre (NBC), Ministry of Agriculture and Forests, Bhutan, 2018)
Report of the Tandem Workshop on the Nagoya Protocol on Access and Benefit-Sharing & The Multilateral System of Access and Benefit-Sharing under the International Treaty on Plant Genetic Resources for Food & Agriculture (ITPGRFA), 29th September 2017, Paro, Bhutan. The workshop was organized by the National Biodiversity Centre (NBC), Ministry of Agriculture and Forests, Bhutan in collaboration with Bioversity International. Financial support was provided from Bioversity International through the project "Strengthening national capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture (GRPI 2)", from UNDP-Bhutan and GEF through their project “Implementing the Nagoya Protocol on Access to Genetic Resources and Benefit Sharing in Bhutan”. The aim of the workshop was to strengthen national capacity and share knowledge on the mutually supportive implementation interface between the Nagoya Protocol and the ITPGRFA, in the context of broader national policy goals; and to identify the core issues of the implementation interface of the ITPGRFA and the Nagoya Protocol.